1992
DOI: 10.1073/pnas.89.24.11973
|View full text |Cite
|
Sign up to set email alerts
|

Borocaptate sodium: a potential boron delivery compound for boron neutron capture therapy evaluated in dogs with spontaneous intracranial tumors.

Abstract: Borocaptate sodium (Na2B12HjjSH) is a boron-carrying compound under consideration for use in boron neutron capture therapy. The biodistribution of boron from borocaptate sodium adminition will partly determine boron neutron capture therapy efficacy and normal tissue radiation tolerance. The biodistribution of boron was determined in 30 dogs with spontaneous intracranial tumors at 2, 6, or 12 hr after intravenous borocaptate sodium infusion. Blood and tissue boron concentrations were measured using inductively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In 1992, Kraft et al studied biodistribution of boron in 30 dogs with spontaneous intracranial tumors after intravenous BSH (55 mg of natural boron/kg of body weight) infusion. They showed that the highest and feasible BNCT boron concentration in tumor tissue was observed at the first assessable time point of 2 h after infusion (35.9 ± 4.6 µg/g), that a high tumor/normal cell boron concentration ratio was achieved, and a subsequent linear decrease to the insufficient level of 7.0 ± 1.1 µg/g was seen at 12 h (indicating optimal time intervals for neutron irradiation) [ 93 ]. In another publication, the authors reported higher mean boron accumulation in extracranial compared to intracranial spontaneous tumors in dogs with maximum levels at 2 h after BSH infusions of the same dose as their previous report.…”
Section: Discussionmentioning
confidence: 99%
“…In 1992, Kraft et al studied biodistribution of boron in 30 dogs with spontaneous intracranial tumors after intravenous BSH (55 mg of natural boron/kg of body weight) infusion. They showed that the highest and feasible BNCT boron concentration in tumor tissue was observed at the first assessable time point of 2 h after infusion (35.9 ± 4.6 µg/g), that a high tumor/normal cell boron concentration ratio was achieved, and a subsequent linear decrease to the insufficient level of 7.0 ± 1.1 µg/g was seen at 12 h (indicating optimal time intervals for neutron irradiation) [ 93 ]. In another publication, the authors reported higher mean boron accumulation in extracranial compared to intracranial spontaneous tumors in dogs with maximum levels at 2 h after BSH infusions of the same dose as their previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs have previously been used in BNCT-related studies to evaluate the RBE of an epithermal beam for brain tissue [ 36 ], the tolerance of normal canine brain to epithermal neutron irradiation in the presence of BPA [ 37 ], and normal tissue tolerance with BNCT mediated by sodium borocaptate (BSH) [ 38 , 39 ]. Kraft et al [ 40 , 41 ] used dogs with spontaneous brain tumors to evaluate BSH biodistribution and implications for BSH-mediated BNCT. These authors stressed the relevance of studying spontaneous tumors as opposed to experimental tumors.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a study including 51 dogs utilizing frameless SRS indicated a median survival time of 399 days for meningiomas indicating that SRS may provide similar outcomes as traditional radiation therapy with only a single episode of anaesthesia and fewer acute adverse side effects . Boron neutron capture therapy has also been evaluated in dogs in a phase I trial with safety demonstrated; initial clinical results similar to that achieved with conventional radiation have been seen . Dogs have also been used in radiation treatment trials evaluating hyperthermia and photodynamic therapy …”
Section: Prognosis and Treatment For Canine Cns Tumoursmentioning
confidence: 99%